Motivational Reasons for Biased Decisions: The Sunk-Cost Effect’s Instrumental Rationality - Domeier, Markus; Sachse, Pierre; Schäfer, Bernd (Frontiers in Psychology, 2018)
The present study describes the mechanism of need regulation, which accompanies the so-called “biased” decisions. We hypothesized an unconscious urge for psychological need satisfaction as the trigger for cognitive biases. In an experimental study (N = 106), participants had the opportunity to win money in a functionality test. In the test, they could either use the solution they had developed (sunk cost) or an alternative solution that offered a higher probability of winning. The selection of the sunk-cost option was the most chosen option, supporting the hypothesis of this study. The reason behind the majority of participants choosing the sunk-cost option seemed to be the satisfaction of psychological needs, despite a reduced chance of winning money. An intervention, which aimed at triggering self-reflection, had no impact on the decision. The findings of this study contribute to the discussion on the reasons for cognitive biases and their formation in the human mind. Moreover, it discusses the application of the label “irrational” for biased decisions and proposes reasons for instrumental rationality, which exist at an unconscious, need-regulative level.